The impact of income diversification on non-performing loans of commercial banks: Empirical evidence from Southeast Asia - Thuy, Vu Xuan; Son, Dinh Van; Dung, MA Ngo Thuy; Anh, Pham Tuan (Edelweiss Applied Science and Technology, 2025)
This study investigates the determinants of the non-performing loan (NPL) ratio (BDR) in 65 listed commercial banks in Southeast Asia from 2016 to 2023, using fixed-effects panel regression with robust standard errors to analyze 440 observations. Data are taken from annual financial reports. The results show that higher income diversification (IND), measured by the Herfindahl-Hirschman Index, unexpectedly leads to a statistically significant increase in BDR (coefficient: 0.0275, p < 0.05). The COVID-19 pandemic also significantly increases BDR (coefficient: 0.0033, p < 0.01). In contrast, a higher capital adequacy ratio (CAR) significantly reduces BDR (coefficient: -0.0013, p < 0.01). Lagged BDR also positively affects current BDR (coefficient: 0.1659, p < 0.05), highlighting the persistence of NPL. Surprisingly, the non-interest income ratio (NIR), loan-to-asset ratio, cost-to-income ratio, and deposit-to-asset ratio do not significantly affect BDR. The findings have important implications for Southeast Asian bank regulators and policymakers, who should focus on sustainable income diversification rather than rapid expansion, as crucial for long-term stability.